2015
DOI: 10.1007/s40865-015-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity in the Development of Homotypic and Heterotypic Antisocial Behavior

Abstract: Introduction This study aimed to contribute to the existing literature by testing whether the same classes of antisocial behavior typically uncovered in the literature would be revealed with the additional information about heterotypic antisocial behavior. We investigated the development of men's antisocial behavior in its homotypic and heterotypic forms from age 12 to 30 years in a large representative sample. Material and methods Data were drawn from the National Longitudinal Study of Adolescent to Adult Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…During the third and fourth waves, respondents were asked about whether they had engaged in criminal behavior in the past 12 months. The criminal behavior measures change from the first and second waves to the third and fourth waves to reflect heterotypic continuity in offending over time, which more accurately captures patterns of long-term offending (Chen and Jaffee 2015). Criminal behavior includes both nonviolent and violent crimes such as “steal something worth more than $50,” “deliberately damage property that didn’t belong to you,” “buy, sell, or hold stolen property,” “you shot or stabbed someone,” “you go into a serious physical fight,” and “you pulled a knife or gun on someone.” Respondents who reported committing any criminal behavior in the third and fourth waves were categorized as criminally persistent and serve as the reference group for all models.…”
Section: Methodsmentioning
confidence: 99%
“…During the third and fourth waves, respondents were asked about whether they had engaged in criminal behavior in the past 12 months. The criminal behavior measures change from the first and second waves to the third and fourth waves to reflect heterotypic continuity in offending over time, which more accurately captures patterns of long-term offending (Chen and Jaffee 2015). Criminal behavior includes both nonviolent and violent crimes such as “steal something worth more than $50,” “deliberately damage property that didn’t belong to you,” “buy, sell, or hold stolen property,” “you shot or stabbed someone,” “you go into a serious physical fight,” and “you pulled a knife or gun on someone.” Respondents who reported committing any criminal behavior in the third and fourth waves were categorized as criminally persistent and serve as the reference group for all models.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is now clear that many individuals with adolescent-onset antisocial behavior continue their antisocial behavior into adulthood [16], though the level of AL's continuing antisocial behavior is much less than that of LCP's. For example, the Dunedin study found that official (court) convictions for violence for males at age 32, which tend to reflect more serious kinds of violence than self-reported violence [7], were much more frequent for LCP than AL individuals: 33% vs. 8% [25]. Indeed, the LCP individuals accounted for 72% of the months spend in jail for the entire male cohort in the study [25].…”
Section: Journal Of Forensic Psychologymentioning
confidence: 99%
“…The two decades plus of research since 1993 has provided overwhelming support for a category of a small group of individuals who engage in early starting, persistent antisocial behavior and who tend to have more risk factors for antisocial behavior than any other group [3,7,8,[15][16][17][18]. The trajectory of offending of individuals in this category has been concisely summarized by Le Blanc [18].…”
Section: Early Starting Life-course Antisocial Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, another issue concerning the measurement of delinquency is that of its continuity. Hitherto, longitudinal studies, which encompass several developmental periods, used-if at all-either of two strategies to maintain continuity of measurement: items were adapted across the age span to ensure that the measures were developmentally appropriate (e. g., Dunedin Multidisciplinary Health and Development Study; see Odgers et al 2008) or studies included new items with ageappropriate acts of delinquency (e.g., National Longitudinal Study of Adolescent Health; see Chen and Jaffee 2015). If the composition of items does not change at all, homotypic continuity is assumed.…”
Section: Measuring Delinquency Across Developmental Periods and Possimentioning
confidence: 99%